THE EFFECT OF SERVICE AND FACILITY QUALITY ON PATIENT SATISFACTION AT THE DARMASRAYA REGIONAL GENERAL HOSPITAL (RSUD) - Taufid, Hidayattul; Harun, Zul Irfan; Aima, M. Havidz; Fitriyeni, Fitriyeni (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
The purpose of this study is to find out and analyze the Quality of Service, Facilities, and Patient Satisfaction of Darmasraya Regency Hospital. The method and type of research used is a type of quantitative research with a survey research method, data was obtained directly through questionnaires to 20 respondents who were family patients of patients at Darmasraya Regency Hospital.  Sample extraction uses the overall sampling technique (total sampling). Data analysis was carried out in several stages, namely 1) Validity Test was tested with Pearson correlation (r count > r table). 2) Reliability tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality Test to find out whether the data is normally distributed or not 4) T test to find out the influence of each independent variable on the dependent variable. 5) F test to determine the influence of Service Quality and Facilities simultaneously on Patient Satisfaction of Darmasraya Regency Hospital. 6) Coefficient of Determination (R²) to find out how much contribution independent variables contribute in explaining dependent variables. Based on the results of the research and discussion that has been stated above, the following conclusions can be drawn:. 1) The Service Quality Variable affects Patient Satisfaction at Darmasraya Hospital. This means that the better the quality of service, the higher the level of Patient Satisfaction. 2) Facility variables have a positive effect on Patient Satisfaction at Darmasraya Hospital. This means that the better the Facility of an institution, the more Patient Satisfaction will increase. 3) Simultaneously the Quality of Service, and Facilities have a positive effect on Patient Satisfaction at Darmasraya Hospital.